THE ANALYSIS OF THE EFFECTS OF MANAGEMENT DECISIONS ON NET SALES IN LARGE CORPORATIONS IN TURKEY - ÖZKAN, Mehmet Serhan (IJRDO - Journal of Business Management, 2016)
Management decisions and general performances of corporations are both importantissues in business. It is an objective to present how much management decisionsinfluence net sales as firm performance indicator in order to reveal the knowledge inquestion.There are 11 sectors and thus 11 sector-leader companies in Borsa İstanbul-30(BIST-30) Index. These companies are examined and many particular results have beenrevealed via the study. The one of them is that in order to explain net sales; marketingexpenses, research expenses and worker numbers are observed to be consistent andeffective independent variables while the other variables not.The other important result is that there is a significant relationship betweenmanagement decisions and net sales of Borsa İstanbul’s large corporations. Therelationship in question have been demonstrated with 11 models out of 11 have strongor very strong determination skill for modelling the variables of net sales